Evaluation of the ixodicide effect of botanical extracts on Rhipicephalus (Boophilus) microplus tick - Rodriguez Molano, Carlos Eduardo; Niño Monroy, Laura Estefanía; Pulido Suárez , Nestor Julián (Universidad Pedagógica y Tecnológica de Colombia, 2022)
Ticks have negatively affected cattle production, causing great economic losses; due to the indiscriminate use of chemical products they have developed resistance, forcing the search for control alternatives, presenting an interest in investigating the acaricidal properties of plant species, the objective of the study was to determine the efficacy of the natural extract Phytolacca bogotensis and Alnus alcuminata in the control in vitro of the adult tick Rhipicephalus (Boophilus) microplus. The method used for the elaboration of the extracts of the analyzed plants was the hot extraction "Soxhlet", and the secondary metabolites were evaluated through qualitative tests. Adult ticks were exposed by the immersion technique to the pure extracts and dilutions. At 24, 48, 72 and 96h post-exposure, mortality was evaluated, taking a mortality of 60% as the minimum effective. The P. bogotensisextract showed effectiveness with the pure extract and the 1:2 dilution, and the pure extract of A. alcuminata did not exceed the minimum effective mortality rate. It was observed that the P. bogotensis extract showed greater efficacy in the control of the adult tick Rhipicephalus (Boophilus) microplus, constituting itself as a source of active principles that contribute to the discovery of ixodicides of natural origin.